Intensity modulated proton therapy for early-stage glottic cancer: high-precision approach to laryngeal function preservation with exceptional treatment tolerability - Held, Thomas; Franke, Henrik; Uzun-Lang, Kristin; Eichkorn, Tanja; Regnery, Sebastian; Kozyra, Katharina; Bauer, Lukas; Plath, Karim; Dyckhoff, Gerhard; Plinkert, Peter K.; Harrabi, Semi B.; Herfarth, Klaus; et al. (Radiation oncology, 2022)
Background: Due to the increasing expertise in transoral laser surgery and image-guided radiation therapy, treatment outcomes have recently improved in patients with early-stage glottic cancer. The objective of the current study was to evaluate intensity-modulated proton therapy (IMPT) as novel treatment option. Methods: A total of 15 patients with T1-2N0 glottic squamous cell carcinoma, treated between 2017 and 2020, were evaluated. Toxicity was recorded according to the Common Terminology Criteria for Adverse Events (CTCAE) v4.03. Results: The majority were T1a/b tumors (66.7%) and no patient had lymph node or distant metastases. The median total dose was 70 Gy relative biological effectiveness (RBE) (range 66–70 Gy RBE). The one- and two-year OS and metastases-free survival were 100%. One patient developed local failure and received salvage laryngectomy. No higher-grade acute or late toxicity was reported. The mean number of CTCAE grade I and II overall toxicity events per patient was 4.1 (95%-[confidence interval] CI 3.1–5.3) and 1.0 (95%-CI 0.5–1.5). Conclusion: High-precision proton therapy of T1-2N0 glottic cancer resulted in exceptional treatment tolerability with high rates of laryngeal function preservation and promising oncological outcome. IMPT has the potential to become a standard treatment option for patients with early-stage laryngeal cancer.
Gesehen am 23.01.2023